3D printing and virtual surgical planning in a difficult Bonebridge case. Issue 1 (2nd January 2019) - Mukherjee, Payal; Cheng, Kai
ABSTRACT: Virtual surgical planning (VSP) is an applied use of 3D printing showing improvement in patient outcome and health costs though its use in ear surgery has not been reported. VSP was applied to Bonebridge (BB) surgery. A 3D printed temporal bone of a patient requiring revision Modified Radical Mastoidectomy (MRM) was used. MRM was performed on the printed bone and BB site selected by drilling a well to fit the dummy device. Following this, this printed bone was scanned and a surgical cutting guide designed and printed for intraoperative use. The cutting guide was a useful aid to translate the preoperative planning to the operating table. VSP can be a useful tool in BB surgery though its benefit is reserved particularly for difficult cases. More applications allow scalability and having planning and printing facilities based at clinical sites, encourage clinical translation as demonstrated in this case.